ANALISIS PRODUKSI DAN EFISIENSI ALOKATIF USAHA BUDIDAYA IKAN NILA MERAH (Oroechromis Sp) DI DESA D TEGALREJO KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS PROVINSI SUMATERA SELATAN - Asri, Rommy Algamar; Arianti, Nyayu Neti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
This study aimed to know: 1) inputs that affect the red tilapia production (output), 2) the allocative efficiency level of the inputs, and 3) the optimum amount of the inputs that must be allocated efficiently. 35 respondents were taken by cencus method. The Cobb Douglass model was used to analyze which factors or inputs such as pond wide, red tilapia fingerlings, feed, manure and labour affect the red tilapia production. The results showed that the pond wide and feed positively affected the red tilapia production, whereasred tilapia fingerlings, manure and labour did not. The inputs allocative efficiency level of pond wide and feed were 1,900 and 1,250 or more than 1. That was meaned those inputs allocation were not efficient yet. Pond wide must to be added to the optimal level 0,96 Ha from 0,49 Ha and feed must to be added from 5.036,000 to 6312,050 kg/production period.